Lost Property and the Materiality of Absence. (June 2021) - Holmes, Helen; Ehgartner, Ulrike
This article explores material loss and develops a new conceptual agenda. Synthesising and developing debates on the sociology of consumption and material culture in combination with those of the sociology of nothing, it argues that material loss is crucial to understanding people's everyday relationships to the material world and to practices of consumption. Abstract notions of absence, nothingness and loss are becoming increasingly intriguing phenomena for sociologists interested in the everyday. However, whilst their theoretical connotations are being discussed more and more, empirical investigation into these phenomena remains somewhat (ironically) absent. This article draws on a recent project exploring lost property, based on qualitative interviews with lost property offices, households and museums. Developing previous work on material affinities and material culture, the authors argue that lost property reveals the enduring relationships people have with objects which are no longer in their possession. These relationships disrupt and develop contemporary debates on the sociology of consumption regarding how objects are devalued, divested and disposed of, as well as how they are acquired, appropriated and appreciated. In turn, we contend that the transformative potential of material loss and absence offers a way of thinking about alternative, non-material practices of accumulation.